Ferrovias: da produção de riquezas ao apoio logístico no Triângulo Mineiro - Silva, Ercília de Fátima Pegorari (2008)
Th is d issertat ion shows the importance of the ra i lways as cata lyt ic in the construct ion and occupat ion of the geographica l space. They appeared in England and of there they dispersed all over the world, ac companying the deve lopment of the industry and the urbanizat ion. In Bra z i l, the ra i lways was fundamental for the transport of the main product , the coffee, of the end of the century XIX to the first decades of the century XX, became responsible a lso for tying the coast to the inter ior of the country, besides the Tr iângu lo Mine iro (Min ing Tr iangle) , through the implantat ion of severa l ra i l companies. The reduced investments in the recast , in the conservat ion and in the acquisit ion of ro l l ing mater ia l , they took the rai l sect ion to the stagnat ion. To minimize that s ituat ion, in the decade of 1990, they happened the privat izat ions and the concessions. In the Tr iângulo Mine iro (Mining Tr iangle) the dea lersh ip is Fe rrovia Centro- At lânt ica (FCA), that it renders services of transport of loads, becoming of that sorts out an important logist ic support for area .